THE EFFECT OF ADDING GTG SOLUTION IN DRINKING WATER ON FINAL BODY WEIGHT, FEED EFFICIENCY, AND INCOME OVER FEED COST OF LOCAL DUCK - TANWIRIAH, WIWIN; Garnida, Dani; Sujana, Endang; Mushawir, Andi; Widyastuti, Tuti (Jurnal Ilmu Ternak Universitas Padjadjaran, 2023)
This research aims to determine the effect of adding GTG solution in drinking water to the body weight gain, final body weight, ration efficiency and income over feed cost in local ducks. This study used 60 male Tasikmalaya local ducks which were divided into 4 treatment groups and then put into 5 pens as replications, so there were 20 pens. Ducks were reared from 1 day to 45 days old. The initial body weight of the ducklings after being weighed had a coefficient of variation of 5.10 %. GTG solution consists of water, ginger juice, turmeric juice, and garlic juice in equal ratios. There were 4 treatments, namely P0 = drinking water + 0% GTG solution, 12 = drinking water + 0.5 % GTG solution, P2 = drinking water + 1% GTG and P3 = drinking water + 1.5% GTG solution. The data were analyzed with ANOVA to determine the effect of the treatment and then subjected to Duncan's test to differentiate each treatment. The parameters measured were body weight gain, final body weight, feed efficiency, and income over feed cost. The results showed that the addition of 1% JKBP solution into drinking water gave the highest body weight gain, final body weight, feed efficiency, and income over feed cost in local ducks.